MONITORING OF SURFACE OBJECTS AND PROCESSES DO IT IN ARCGIS SOFTWARE (IN THE EXAMPLE OF SAMARKAND REGION) (Proceedings of International Educators Conference, 2024)
Monitoring of surface objects in the ArcGis program, analysis of surface processes using the classification method. And studying the effects on surface objects with the help of classification data. For this, using space images captured by Landsat satellites.